Pelatihan Manajemen Koperasi dan Kelembagaan Koperasi bagi Pengawas Koperasi di Kota Cimahi Propinsi Jawa Barat - Lely Savitri Dewi (E-Coops-Day, 2023)
In order to improve the competency of management, especially cooperative supervisors inimplementing management and cooperative functions, the Cimahi City Cooperative Office consistently carries out various technical guidance and training. One form of this collaboration is with the IKOPIN University Research and Community Service Institute through cooperative technical guidance activities on November 17 and 18 2022. One of the materials provided is the implementation of the principles of cooperative management and cooperative institutions, especially aspects of supervision. The purpose of this material is for participants, namely cooperative supervisors, to explore and implement management principles which include planning, organizing,directing, and supervising, especially in cooperatives.